ANALISIS FRAMING PEMBERITAAN BOM SARINAH DI KOMPAS.COM DAN MERDEKA.COM - Sinaga, Kumala Citra Somara; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Terrorism is not a new case in Indonesia, several months ago Indonesia came to be terrorism action attack that happened in Sarinah territorial, at central of Jakarta. The bombed was happening in 14 january 2016, blowed up several times Sarinah crossing territory. â€œBom Sarinahâ€ is the first bomb since 2009 ago in Indonesia. Related with this case development, media pushed down to giving the latest information to people, by online media. Online media is theThis research using cualitative method, with analysis of framing Zhongdang Pan and Koscki Models. The objects of this research are the news that related with cases of â€œBom Sarinahâ€ in kompas.com and merdeka.com which taken by cascading everyday, based by different topics from 14 January 2016 â€“ 18 January 2016.From the reconstruction or framing, kompas.com was blowing up the human interest side from the police department, it is showed how kompas.com brought the image of police department when treated the case of â€œBom Sarinahâ€ (news 16 January 2016) and the source that used by kompas.com only have one source, the police department (news 14-18 January 2016) while merdeka.com taking from any resources or interests, it showed up from the news of merdeka.com that have not any sides of any specific resources (news 14-18 January 2016), the point of view which taken from the news is â€žwhat is happening at the fieldâ€Ÿ and using several resoursces for making news, any of them are society and BNPT chief development.Keyword : kompas.com, merdeka.com, and Human Interest